Abraham Willink: impulsor de la descentralización de la entomología argentina - Claps, Lucia Elena (2013)
We present a synthesis of the main activities developed by Abraham Willink (1920-1998) in relation to science in Argentina, particularly referring to entomology. We provide information about his personal life, his career at the university, particularly as related to the development of postgraduate studies and training of human resources in the Facultad de Ciencias Naturales e Instituto Miguel Lillo de la Universidad Nacional de Tucumán, Argentina. We highlight his background in the systematics and biogeography of higher Hymenoptera and his important contribution to the formation and maintenance of the insect collection of the Instituto Miguel Lillo. We also highlight his great interest in the decentralization of science, especially in Entomology in Argentina. We provide information on scientific achievements and the recognition he received from students and colleagues from around the world. Finally, we highlight his personal qualities that reflect the human warmth that characterized him as a teacher of several generations of biologists, not just entomologists.